Analisis Nilai SPF Ekstrak Etanol, Fraksi N-Heksana, Fraksi Etil Asetat Dan Fraksi Air Kulit Batang Kawista (Limonia Acidissima Groff) - Fenny Wiji Astuti; Tunik Saptawati; Anifatus Sa’adah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Indtoduction : Free radicals that come from sunlight can cause cell damage and death because they are carcinogenic. SPF is the effectiveness of a sunscreen in protecting the skin from the sun. Kawista stem bark (Limonia acidissima Groff) has potential as a sunscreen. Purpose: to analyze the SPF value of ethanol extract, n-hexane fraction, ethyl acetate fraction and water fraction. Method : Extraction by maceration method with 96% ethanol and fractionation by liquid-liquid extraction method. Phytochemical screening. SPF analysis by spectrophotometric method with the Mansur equation. One-way ANOVA statistical analysis. Results: The SPF values ​​of ethanol extract, ethyl acetate fraction, water fraction and n-hexane fraction respectively along with sunscreen protection categories were SPF 12.77 (maximum protection), SPF 11.77 (maximum protection), SPF 11.67 ( maximum protection) and SPF 7.146 (extra protection). Conclusion: The highest SPF value was found in ethanol extract as a semi-polar solvent. The lowest SPF value was obtained in the n-hexane fraction as a non-polar solvent.